A 2, 2′-diphosphinotolane as a versatile precursor for the synthesis of P-ylidic mesoionic carbenes via reversible C–P bond formation. Issue 10 (29th January 2021) - Wagner, Hannah K.; Wadepohl, Hubert; Ballmann, Joachim
Abstract : A metal-templated synthesis of cyclic (aryl)(ylidic)mesoionic carbene complexes (CArY-MICs ) is presented. In the case of molybdenum carbonyls, the crucial P–C bond formation, which occurs during CArY-MIC formation, was found to be reversible. Abstract : A metal-templated synthetic route to cyclic (aryl)(ylidic) mesoionic carbenes (CArY-MIC s) featuring an endocyclic P-ylide is presented. This approach, which requires metal templates with two cis -positioned open coordination sites, is based on the controlled cyclisation of a P, P ′-diisopropyl-substituted 2, 2′-diphosphinotolane (1 ) and leads to chelate complexes coordinated by a phosphine donor and the CArY-MIC carbon atom. The C–P bond formation involved in the former partial cyclisation of 1 proceeds under mild conditions and was shown to be applicable all over the d-block. In the presence of a third fac -positioned open coordination site, the P–C bond formation was found to be reversible, as shown for a series of molybdenum complexes. DFT modelling studies are in line with an interpretation of the target compounds as CArY-MIC s.